These Strange Criminals : an Anthology of Prison Memoirs by Conscientious Objectors from the Great War to the Cold War. - Brock, Peter (Heritage., 2004)
Sometimes intensely moving, and often inspiring, these memoirs show that in some cases, individual conscientious objectors - many well-educated and politically aware - sought to reform the penal system from within either by publicizing its dysfunction or through further resistance to authority.